A note on fractional-type models of population dynamics - Caratelli, Diego; Ricci, Paolo Emilio (Mathematical Modelling and Analysis, 2024)
The fractional exponential function is considered. General expansions in fractional powers are used to solve fractional population dynamics problems. Laguerretype exponentials are also considered, and an application to Laguerre-type fractional logistic equation is shown.